Depressive and Anxiety Symptoms Are Predictors of Seizure Recurrence in Adults With Newly Diagnosed Epilepsy - Zhong, Rui; Chen, Qingling; Zhang, Xinyue; Li, Nan; Lin, Weihong (Frontiers in Psychiatry, 2021)
Abstract Objective: To investigate whether emerging depressive and anxiety symptoms are predictors of seizure recurrence in a cohort of patients with newly diagnosed epilepsy (PWNDE) who did not have a history of psychiatric diagnosis. Methods: A cohort of 283 PWNDE were psychiatrically assessed before antiseizure medication (ASM) therapy and were followed for 12 months to assess seizure recurrence. The influence of depressive and anxiety symptoms score on seizure recurrence was assessed using univariate and multivariate binary logistic regression analysis. Receiver operating characteristic (ROC) curve analysis was utilized. Results: A total of 283 individuals were included in final analysis, and 115 patients (40.6%) experienced seizure recurrence during follow-up. In multivariate logistic regression analysis, NDDI-E and GAD-7 score were associated with an increased risk of seizure recurrence with an adjusted OR of 1.360 (CI: 1.176–1.572; P＜0.001) and 1.101 (CI: 1.004–1.209; P=0.041), respectively. Additionally, the adjusted OR and 95% CI of seizure recurrence for the“high NDDI-E score and high GAD-7 score”vs“not high NDDI-E score and not high GAD-7 score”was 7.059 (3.521–14.149) (P for trend ＜0.001). Conclusion: We found that an emergence of new psychiatric symptoms including depressive and anxiety symptoms were predictors of seizure recurrence in adults with newly diagnosed epilepsy who did not have psychiatric history.